Characterization of electroencephalographic and biochemical responses at 5-HT promoting drug-induced onset of serotonin syndrome in rats - Ma, Zhiyuan (J Neurochem, 2013)
Many psychotropic substances used either for medications or illicit recreational purposes are able to produce an increase in extracellular serotonin (5HT) in the CNS. 5HT is well known to improve mood, however, only when the levels of its release are in an appropriate range. Excessive 5HT is harmful, and will generally result in serotonin syndrome. To date, clinical diagnosis of serotonin syndrome relies exclusively on observation of symptoms because of a lack of available laboratory tests. The goal of the present study was to characterize the onset of the syndrome using laboratory settings to determine excessive 5HT-evoked neurological abnormalities. Experiments were carried out in rats with the syndrome being elicited by three groups of 5HT-promoting drugs: 1) (±)-3,4-methylenedioxymethamphetamine (MDMA); 2) a combination of the monoamine oxidase inhibitor clorgyline with the 5HT precursor 5-hydroxytryptophan; 3) clorgyline combined with the serotonin-selective reuptake inhibitor paroxetine. The onset of the syndrome was characterized by electroencephalography (EEG), tremor and brain/plasma 5HT tests. We found that a mild syndrome was associated with reduced EEG amplitudes while a severe syndrome strongly with seizure-like EEG activity and increased tremor activity. The occurrence of the syndrome was confirmed with microdialysis, showing excessive 5HT efflux in brain dialysate and the increased concentration of unbound 5HT in the plasma. Our findings suggest that the syndrome onset can be revealed with EEG recording, measurements of tremor activity and changes of unbound 5HT concentration in the plasma.